Design of A Portable Solid-Fuel Rocket Stove - Aljufri, Aljufri; Putra, Reza; Rahman, Abdul; Mardian, Rikki (Jurnal Teknologi, 2024)
The depletion of fossil fuels is a hot topic of discussion these days. This is due to the increasing use of fossil fuels in human life. In terms of the increase in fuel and gas prices, we realise that the energy consumption that is increasing from year to year is not balanced with the availability of energy sources, which affects households that use fuel in the cooking process. So a design was carried out to make an ergonomic solid fuel stove with the aim of not using fuel anymore in the cooking process, in this design, the stove is designed to be more flexible and get a portable biomass rocket stove design by considering social aspects, performance, local resources, economy, environmentally friendly. Biomass fuels are solids, liquids or gases produced from organic matter.. Biomass fuels used in solid fuel stoves such as firewood, charcoal, briquettes and pellets. Each biomass fuel has different properties and characteristics. The designed portable rocket stove consists of several main parts namely combustion chamber, chimney, air duct, pan spot and cassing, using stainless steel material. The test results include combustion chamber and water temperature during the process, thermal efficiency, combustion rate and specific fuel consumption under cold start and hot start conditions. After hot start, it is found that the use of a chimney on a portable stove designed using coconut shell fuel is more effective than without a chimney. Shorter boiling time of 1 minute, greater combustion rate of 0.13 grams/minute, higher thermal efficiency of 2% and lower specific fuel consumption of 9.11 grams/litre of water when the stove uses a chimney.